2014
DOI: 10.1002/jms.3396
|View full text |Cite
|
Sign up to set email alerts
|

Study of solid/gas phase photocatalytic reactions by electron ionization mass spectrometry

Abstract: This paper describes a novel methodology for the real-time study of solid-gas phase photocatalytic reactions in situ. A novel reaction chamber has been designed and developed to facilitate the investigation of photoactive materials under different gas compositions. UV irradiation in the wavelength of ranges 376-387 and 381-392 nm was provided using specially designed high efficiency light emitting diode arrays. The experiments used air containing 190 ppm NO2 in a moist environment with a relative humidity of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Anatase is one of the polymorphs and is widely studied for its photocatalytic properties when exposed to UV radiation. Previous researchers have investigated the use of titanium dioxide and its photocatalytic reactions in a wide range of applications such as water treatment [12][13][14], air purification [15][16][17][18][19] self-cleaning surfaces [20][21][22][23][24][25][26] or for the development of new super hydrophilic surfaces [21].…”
Section: Titanium Dioxide and Photocatalysismentioning
confidence: 99%
“…Anatase is one of the polymorphs and is widely studied for its photocatalytic properties when exposed to UV radiation. Previous researchers have investigated the use of titanium dioxide and its photocatalytic reactions in a wide range of applications such as water treatment [12][13][14], air purification [15][16][17][18][19] self-cleaning surfaces [20][21][22][23][24][25][26] or for the development of new super hydrophilic surfaces [21].…”
Section: Titanium Dioxide and Photocatalysismentioning
confidence: 99%
“…To assess the photocatalytic activity of TiO 2 powders in the gas phase, a mass spectrometer was employed due to its ability to monitor a range of species simultaneously. The system has been reported previously in detail [14][15][16], including the ionic species and corresponding masses commonly formed in the gas phase [15]. A schematic diagram of the system is shown in Figure 1.…”
Section: Photocatalytic Degradation Of Gaseous Pollutantsmentioning
confidence: 99%
“…Gas cylinders are connected via flowmeters to the reactive chamber. One output is connected to the detector[15].…”
mentioning
confidence: 99%
“…Recent developments in the application of electron ionisation mass spectrometry for the study of photo-catalytic activity have demonstrated the suitability and reliability of this approach for multiple pollutants. Studies have differentiated between rutile and anatase forms of TiO 2 under irradiation at different wavelengths in the UVA range [25].…”
Section: Introductionmentioning
confidence: 99%